Perencanaan Kurikulum Dan Pembelajaran - Syafruddin Nurdin; Muhammad Kosim; Tabrani Tabrani (Departement of Mathematics Education, 2023)
Curriculum is a set of plans and arrangements regarding objectives, content, and learning materials as well as the methods used as guidelines for organizing learning activities to achieve certain goals. The curriculum planning is expected to provide teaching and learning opportunities to foster students/students towards the desired behavior change and assess the extent to which the changes occur in students/learners and must be based on a clear concept of various things that make life better. well, the characteristics of society now and in the future, as well as basic human needs.